2021
DOI: 10.1128/mbio.03132-20
|View full text |Cite
|
Sign up to set email alerts
|

Persistence of Human Bocavirus 1 in Tonsillar Germinal Centers and Antibody-Dependent Enhancement of Infection

Abstract: Human bocavirus 1 (HBoV1), a nonenveloped single-stranded DNA parvovirus, causes mild to life-threatening respiratory tract infections, acute otitis media, and encephalitis in young children. HBoV1 often persists in nasopharyngeal secretions for months, hampering diagnosis. It has also been shown to persist in pediatric palatine and adenoid tonsils, which suggests that lymphoid organs are reservoirs for virus spread; however, the tissue site and host cells remain unknown. Our aim was to determine, in healthy n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
30
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 20 publications
(30 citation statements)
references
References 59 publications
0
30
0
Order By: Relevance
“… 27 A study in Finland showed that HBoV persisted in the respiratory tract for long periods, increasing the chance of co-detection with other viruses. 28 Emanuels et al. also found a high prevalence of HBoV and other pathogens in Nepal.…”
Section: Discussionmentioning
confidence: 91%
“… 27 A study in Finland showed that HBoV persisted in the respiratory tract for long periods, increasing the chance of co-detection with other viruses. 28 Emanuels et al. also found a high prevalence of HBoV and other pathogens in Nepal.…”
Section: Discussionmentioning
confidence: 91%
“…Mostly in children, but infrequently also in adults, HBoV1 DNA is able to persist in tonsils, which have been suggested to be reservoirs for virus spread. HBoV1 has been shown to localize in tonsillar germinal centres (GCs) and to invade GC B cells and monocytes through antibody-dependent enhancement (ADE) of infection via the Fc receptor [ 30 ]. More studies of the clinical significance of latency, OAS and ADE are much needed to clarify these interesting phenomena.…”
Section: Discussionmentioning
confidence: 99%
“…The PCR products of target amplicons, spliced VP and non-spliced NS1, were cloned into pSTBlue vector and served as assay controls. RNA polymerase II (RPII), human housekeeping mRNA, was quantified for each RNA prep as internal control, as described ( Xu et al, 2021 ).…”
Section: Methodsmentioning
confidence: 99%
“…B19V DNA has been detected in various tissue types including synovium, skin, heart, liver, muscle, tonsil, testis, brain, salivary glands, bone, and bone marrow ( Cassinotti et al, 1997 ; Söderlund et al, 1997 ; Eis-Hübinger et al, 2001 ; Söderlund-Venermo et al, 2002 ; Vuorinen et al, 2002 ; Lotze et al, 2004 ; Hobbs, 2006 ; Norja et al, 2006 ; Manning et al, 2007 ; Adamson-Small et al, 2014 ; Toppinen et al, 2015a ; Pyöriä et al, 2017 ; Santonja et al, 2017 ), of both symptomatic and healthy individuals. HBoV DNAs have been detected in tonsils, intestine, and heart ( Kuethe et al, 2009 ; Kapoor et al, 2011 ; Proenca-Modena et al, 2012 ; Schildgen et al, 2013 ; Abdel-Moneim et al, 2016 ; Qiu et al, 2017 ; Ivaska et al, 2019 ; Xu et al, 2021 ). Associations of B19V or HBoV infection with inflammatory bowel diseases, such as ulcerative colitis (UC), or gastrointestinal tumors have been suggested, but the causative role has not been verified ( Li et al, 2007 ; Pironi et al, 2009 ; Schildgen et al, 2013 ; Abdel-Moneim et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation